HISTORY AS A SCHOOL SUBJECT IN NATIONAL CURRICULA FOR ESTONIAN GENERAL COMPREHENSIVE SCHOOLS IN 1874-2015. - Haljasorg, Heiki; Läänemets, Urve (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This study is focused on development of the content of history as a school subject in Estonian general comprehensive schools in 1874-2015. Selection of the content for learning has been influenced by the socio-political context and ideology in all times reflecting the officially recognized and accepted values. Theoretical analysis of selection of the content for history learning in Estonian general comprehensive schools is based on the works of de Tracy, Marx, Engels, Maritain, Althusser, Habermas, Žižek, Mannheim, Foucault, Popper, Gellner, de Beauvoir, Tyler, Taba, Goodson, Pinar, Kelly and Autio. All curriculum documents of the mentioned period have been analysed considering their aims, content of learning, time allotted for learning, and methods recommended in a thematic monograph. This article is focussed on aims and principles for selection of the content of history learning in Estonian general comprehensive schools, influenced by ideologies and contexts at different times.